Confronting the Climate Crisis: Fossil Fuel Hegemony and the Need for Decarbonization, Degrowth, and Democracy - Nyberg, Daniel; Wright, Christopher (Journal of management studies, 2025)
In this Counterpoint, we argue for the importance of social movements in responding to the climate crisis by challenging the taken‐for‐granted practices and policies of corporate capitalism. These challenges politicize what is seen as ‘common sense’ and show that there are alternatives to the dominant social order of fossil‐fuelled economic growth. More specifically, we set out three ways to minimise future harm and suffering by discussing (i) the required decarbonisation of the economic system, (ii) the eventual degrowth needed to address the existing crisis and avoiding the creation of another, and (iii) the strengthening of democracy essential to breaking fossil fuel dependence. Challenges to corporate capitalism are often accused of being naïve and unrealistic, but responding to climate change demands an epochal rethink of what should be seen as ‘sensible’.